Impact of Corporate Social Responsibility Activities on Customer Value Co-creation Behaviour in Pakistan’s Banking Industry - Muhammad, Mubushar (Universiti Malaysia Sarawak (UNIMAS), 2020)
Banking industry of Pakistan has been facing the problem of disconnection between customers and management due to their differences in priorities. Without proper course of action, the banking industry will fail to retain the customers. Corporate social responsibility provides a platform on which corporations address the interest of stakeholders in more effective ways. This study investigates the impact of stakeholders-focused CSR activities (customer, local community, employees and suppliers) on customer value co-creation behaviour. The objective of this study to examine the effect of relationship marketing orientation (RMO) as a mediator between CSR activities and customer value co-creation behaviour in banking industry of Pakistan. For this purpose, a set of data was collected from 453 banking customers from Islamabad/Rawalpindi through questionnaires. PLS-SEM was employed to analyse the data while measurement model and structure equation modelling were evaluated for model fitness. The study demonstrates that CSR activities have positive impacts on customer value co-creation behaviour. Relationship marketing orientation (RMO) partially mediates between customer-focused, employee-focused CSR activities and customer value co-creation behaviour. While RMO does not mediate between local community-focused, supplier-focused CSR activities and customer value co-creation behaviour. This study offers insights for top executives in banking industry who can minimize the disconnection between customers and management through customize CSR activities.